PHARMACOECONOMIC ANALYSIS OF CHICKENPOX IMMUNE PREVENTION EFFECTIVENESS IN THE INFANT ORPHANAGE INMATES - D. V. Raiskii; A. A. Dzhumagaziev; E. I. Dzhal'mukhamedova; I. E. Kvyatkovskii (Педиатрическая фармакология)
Background. Chickenpox is the second most common cause of pediatric infectious pathologies. Specific chickenpox immune prevention has been in use around the world for more than 20 years. The main reasons why chickenpox vaccine has not been included into the national immunization schedule in the territory of the Russian Federation is high price of imported vaccines and the lack of effective and inexpensive Russian counterparts, which is why economic feasibility of expenses on immune prevention against this disease is doubtful. The study was aimed at assessing pharmacoeconomic effectiveness and safety of chickenpox immunization of the infant orphanage inmates on the basis of the retrospective analysis of chickenpox incidence. Methods. Statistical data of the specialized infant orphanage (overall hospital admission rate and chickenpox incidence) for 10 years (2004–2013) have been compared with one-year chickenpox incidence among the children immunized with hypodermic freeze-dried vaccines based on the attenuated Varicella zoster virus (OKA strain) reproduced in the culture of diploid MRC-5 cells. Results. Significance of chickenpox in the morbidity structure of the infant orphanage inmates aged 0-4 years has been demonstrated. Conclusions. Retrospective pharmacoeconomic analysis helped to confirm effectiveness and financial viability of immunizing infant orphanage inmates against chickenpox.